Public Satisfaction towards Land Titling Project for Agricultural Sector (A Case Study in Polewali Mandar District, West Sulawesi) - Belly Sultrawijaya; Andy Fefta Wijaya; Hamidah Nayati Utami (Wacana Journal of Social and Humanity Studies, 2013)
The objectives of this research are to assess the public satisfaction towards the implementation of this land titling project, and to examine to what extent the relationship between the service quality of Badan Pertanahan Nasional (BPN) and farmers satisfaction in Polewali Mandar. Â Finally, to recommend possible improvement for the implementation of Land titling project for agricultural sector. This study used the type of explanatory research with the quantitative approach, and focused on the agency that provide service to the public. Level of community satisfaction was used as a dependent variable. Then, as the independent variable were the assurance, cost, time and product. Research indicates that farmers are satisfied with the services provided by BPN officials through this project. The results of hypothesis tests indicate that all variables have not only simultaneously, but also partially effect towards public satisfaction Furthermore, time was the substantial one. BPN should give attention deal with cost and time factor in order to increase their service quality to public. Keywords: Land titling project, agricultural sector, public satisfaction.